Endolysins: targeting Streptococcus pneumoniae in its major anatomical niches of infection and addressing the hurdles - Castallanos, Giovanna; Gonzalez-Juarbe, Norberto; Nelson, Daniel C. (Frontiers in Microbiology, 2025)
Streptococcus pneumoniae is responsible for causing a range of diseases, from self-limiting otitis media to more severe disease such as pneumonia, sepsis, and meningitis. Vaccines and antibiotics have successfully decreased this disease burden; however, serotype replacement due to vaccines and antibiotic resistance remain issues pointing to the need for further research into alternative methods of treatment. S. pneumoniae continues to pose a global threat to young children and the elderly. Endolysins, which function as peptidoglycan hydrolases, are an attractive alternative treatment given their rapid bactericidal activity, specificity, and lack of noted resistance. This review considers the uses of endolysins within the main niches of infection for S. pneumoniae: pulmonary, middle ear, and the bloodstream and central nervous system. Therapeutic hurdles, such as delivery and mechanical barrier challenges, are discussed and endolysin-focused solutions to circumvent these challenges are proposed. The ability to address niche-specific hurdles using endolysins will allow for an increase in effective therapies against S. pneumoniae.